Kelps on the move: Potential future distribution areas in the face of climate change, on the Pacific coast of South America - Milen Duarte; Natalia Sanhueza; Julio A. Vásquez; Fadia Tala; Alejandra V. González (PLoS ONE, 2025)
Kelp forests are critical marine ecosystems that offer key services such as habitat, coastal protection, carbon sequestration, and support for fisheries. Along the temperate Pacific coast of South America, however, these seaweeds have historically been subjected to intense exploitation pressure, given their value as an economic resource. Additionally, they are impacted by oceanographic and climatic factors such as ENSO (El Niño-Southern Oscillation) event and ongoing climate change. The combined effects of these stressors pose a significant threat to their biomass and geographic distribution. Species distribution models under four representative concentration pathways for 2050 were used to assess the current and future potential distribution of two endemic intertidal kelp species, Lessonia berteroana and Lessonia spicata, which represent two of the four primary kelp species targeted by regional fisheries in the region. This approximation allows us to identify future areas of persistence (retained), retreat (lost), and expansion (gained). The results show that the environmental variables that mainly affected the potential distribution were salinity in L. berteroana and surface water temperature for L. spicata. The predictive models suggest that for L. berteroana, the lost area could reach 60.6%, and retained areas could account for 31.6% of the current area. Similarly, for L. spicata, the models indicate a potential loss of 58.6%, with retained areas comprising approximately 58.2% of the current area. Therefore, models predict a significant contraction could lead to the local disappearance of Lessonia species between 14° S and 25° S, profoundly altering coastal ecosystems and diminishing the critical ecosystem services they provide. Our modeling results underscore the urgent need for informed management and conservation strategies for kelp forests, which serve as vital ecosystem engineers. This research is especially critical in the face of climate change and ongoing anthropogenic pressures such as overexploitation. The study provides a robust scientific foundation for proactive measures to mitigate kelp forest decline and preserving their invaluable ecosystem functions along the Pacific coast of South America.